Understanding Reluctance to Seek Professional Help for Mental Health Issues and Recommendations for Mental Health Startup: Case Study of Ashwa - Poerwanto, Zenden Kurniawan; Qastharin, Annisa Rahmani (Proceedings International Conference on Education Innovation and Social Science, 2023)
Mental health issues are starting to surface because the pandemic has made many people feel lonely, stressed, depressed, and to the point of doing self-harm and suicidal. A mental health platform is developed hoping to help solve this problem. However, study discovered that young adults between 18 and 24 years old were the least likely to receive mental health care. This research will focus on finding why adolescents are reluctant to seek professional help and recommendations for mental health startups. Qualitative methods will be used in this research, with data collected by semi-structured interviews towards the adolescents and psychologist expert and analyzed using the three step coding and triangulation. This research is expected to find the barriers in seeking professional help in young adults that affects the uses of a professional mental health service platform.